CFRP-Based confinement strategies for RC columns-experimental and analytical research - Ferreira, Débora (2009)
The present work aims to compare the confinement effectiveness of full and partial wrapping of concrete elements under compression loads. The main results of the experimental program are presented and analysed. The Lam and Teng analytical model was applied to predict the compression stress-strain behaviour of concrete column elements partially confined by strips of CFRP lay-up sheets. The model performance is assessed using the experimental results.